APLIKASI PENDEKATAN SIX SIGMA UNTUK PERBAIKAN KUALITAS PADA PROSES PEMBUATAN TANK WASHER - Anjar Suprayogi (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
PT. Laksana Teknik Makmur is a manufacturing company engaged in the manufacture of car accesories in Indonesia. One of the products produced is a tank washer with a high defect rate in the production process of 11 percent. This study uses the DMAIC method (Define, Measure, Analyze, Improve, Control) as a tool to solve problems about improving the quality of the process of making tank washer. The initial analysis for Define shows that CTQ (Critical to Quality) is the largest defect of the wave, which is 4.1 percent of the total defects of tank washer. From the measurement results in the Measure stage, the DPMO value is 108475 with Sigma Level 2.73. Then Analyze is done to get any factors that cause wave defects. On the Improve stage using Ishikawa's method, the results of the new Standard Operating Procedure are recommended. In the final stage, Control is carried out after the implementation of the new SOP for 1 month, the result is that the wave defect value drops to 2 percent and the Sigma Level value increases to 3.326 with the value of DPMO 20424.